Civil Servant Pension Administration Services in Remote Regional Governments : A Review of Public Administration Literature - Agustino Yamlean; Dian Ferriswara; Fedianty Augustinah; Sri Kamariyah (International Journal of Humanities and Social Sciences Reviews, 2026)
Civil servant pension administration is a vital yet insufficiently studied public service function within decentralized governance systems, particularly in remote and peripheral local governments where administrative capacity and service accessibility are limited. Although pension policies are nationally standardized, their local-level implementation often reveals disparities in institutional resources, human capital, coordination mechanisms, and infrastructure, leading to uneven service quality and increased administrative burdens for retirees. This literature review aims to synthesize and critically examine scholarly discussions on civil servant pension administration from the perspectives of public service delivery, administrative capacity, and Public Human Resource Management (Public HRM), with a focus on remote and peripheral governance contexts. Employing a narrative–systematic literature review approach, the study analyzes peer-reviewed international journal articles using thematic analysis and conceptual synthesis. The review identifies four dominant themes: the procedural and coordination-intensive nature of pension administration; persistent administrative capacity constraints involving human resources, institutions, and systems; the exacerbating effects of geographic isolation and spatial inequality on service delivery; and the strategic yet underrecognized role of pension administration within public sector HRM and lifecycle governance. The findings suggest that pension administration challenges in remote regions reflect structural capacity mismatches inherent in decentralized systems rather than isolated implementation failures. This review contributes theoretically by integrating public service theory, administrative capacity, and Public HRM within a peripheral governance framework, and practically by emphasizing the need for context-sensitive, capacity-oriented pension service reforms to promote service equity, accountability, and organizational legitimacy in local governments.